An Integrative Framework for Developing Comprehensive Examinations to Measure Student Social Work Competencies. (3rd July 2018) - Jensen, Todd M.; Strom-Gottfried, Kimberly J.
ABSTRACT: Social work and other professions are endeavoring to promote student proficiency with respect to core competencies of the discipline, and the attainment of these competencies must be demonstrated objectively in some way. This article provides an illustrative guide for social work educators seeking to develop comprehensive examinations to assess students' acquisition of professional competencies, particularly at the master's level and across generalist and specialization levels of practice. An integrative framework is presented, highlighting 5 central stages of examination development: planning, creating and implementing, evaluating, revising, and perpetuating. These stages are illustrated with a case example, followed by key conclusions, methodological considerations, and other implications for moving forward on efforts to effectively develop examinations to measure student social work competencies.